Sandbox Sebagai Instrument Hukum Terhadap Perkembangan Inovasi Teknologi Sektor Keuangan Di Indonesia - Anggunsuri, Upita (Nagari Law Review, 2024)
This research aims to analyze the sandbox as a legal instrument for development of financial sector technology innovation in Indonesia. This research endeavors to answer the following questions what is the mechanism of sandbox as a legal instrument for development of financial sector technology innovation in Indonesia, and What are the challenges of Sandbox as a legal instrument for development of financial sector technology innovation in Indonesia. The research method is Normative juridical. The research concludes the stipulation of OJK Regulation Number 3/2024 On The implementation Of Financial Sector Technology Innovation (ITSK) have several changes namely the scope of the financial sector technology innovation not only digital ecosystem but also conventional financial services institutions, the sharia financial services sector, the legal protection and legal certainty for consumers, asset crypto etc (Artikel 1).The determination of the result feasibility sandbox trial has an impact to create participants' perceptions of the feasibility model standards that appropriate to the innovation criteria according to the OJK. The criteria is a form of OJK recognition of the innovation criteria that must be carried out participant sandbox. This condition certainly provides clarification to other participants related to the innovation criteria implemented by the OJK as stated in SEOJK No. 5 of 2024. Furthermore, the ability of government to formulate sandbox legal instruments should be supported by the availability of competent and competitive human resources related to developing digital financial economy products, services and business models that appropriate to face the challenges and market needs of the financial services sector in Indonesia